Facet-Control versus Co-Catalyst-Control in Photocatalytic H-2 Evolution from Anatase TiO2 Nanocrystals - Qin, Shanshan; Shui, Lancang; Osuagwu, Benedict; Denisov, Nikita; Tesler, Alexander; Schmuki, Patrik (ChemistryOpen, 2022)
Titanium dioxide (TiO2) and, in particular, its anatase polymorph, is widely studied for photocatalytic H-2 production. In the present work, we examine the importance of reactive facets of anatase crystallites on the photocatalytic H-2 evolution from aqueous methanol solutions. For this, we synthesized anatase TiO2 nanocrystals with a large amount of either 001 facets, that is, nanosheets, or 101 facets, that is, octahedral nanocubes, and examined their photocatalytic H-2 evolution and then repeated this procedure with samples where Pt co-catalyst is present on all facets. Octahedral nanocubes with abundant 101 facets produce >4 times more H-2 than nanosheets enriched in 001 facets if the reaction is carried out under co-catalyst-free conditions. For samples that carry Pt co-catalyst on both 001 and 101 facets, faceting loses entirely its significance. This demonstrates that the beneficial role of faceting, namely the introduction of 101 facets that act as electron transfer mediator is relevant only for co-catalyst-free TiO2 surfaces.
CRIS-Team WoS Importer:2022-02-11